2016
DOI: 10.15406/mojamt.2016.02.00019
|View full text |Cite
|
Sign up to set email alerts
|

Should Voluntary "Self-Exclusion" by Gamblers be used as a Proxy Measure for Problem Gambling?

Abstract: Self-exclusion practices typically refer to the possibility for gamblers to voluntarily ban themselves from playing all (a selection of) games over a predetermined period. The period of exclusion can typically be chosen by the gambler although some operators have non-negotiable self-exclusion periods. Selfexclusion in both online sites and offline venues has become an important responsible gambling practice that is widely used by socially responsible operators. Auer, Littler and Griffiths. [1] briefly overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Although using payment data to build indicators for online problem gambling may appear to be a good option, using VSE as a proxy measure for problem gambling might not be. This is due to the fact that not all customers choose to use VSE because of a problem with their gambling [ 29 , 40 ]. For example, in the aforementioned study conducted by Haeusler, it was reported that 23.3% of customers that used VSE in January 2015 had no deposit payments at all in the year before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although using payment data to build indicators for online problem gambling may appear to be a good option, using VSE as a proxy measure for problem gambling might not be. This is due to the fact that not all customers choose to use VSE because of a problem with their gambling [ 29 , 40 ]. For example, in the aforementioned study conducted by Haeusler, it was reported that 23.3% of customers that used VSE in January 2015 had no deposit payments at all in the year before.…”
Section: Introductionmentioning
confidence: 99%
“…VSE has been used as a proxy measure for problem gambling in a number of studies [ 16 , 42 , 43 , 44 ]. Although it is very convenient and used in several studies, using VSE as a proxy measure for problem gambling may not always be the best approach, especially when accounting for online VSE [ 40 ]. Although there are several studies that have used VSE as a proxy measure of online problem gambling, little published empirical research has been carried out on its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…When gambling behaviour of the bwin subscribers was compared to a group of control subscribers, indices of the intensity of gambling activity (e.g., total number of bets made, number of bets per betting day) for inplay sports bettors most differentiated those who had triggered the responsible gambling alert from the control group. A limitation of this particular study was that triggering an RG feature does not serve as a guaranteed indicator that the user has experienced a gambling-related problem (Gray et al 2012;Griffiths and Auer 2016;Nelson et al 2008). This supports previous research showing that those using responsible gambling tools such as limit-setting ) are more likely to engage in in-play betting than those who do not use such RG tools.…”
mentioning
confidence: 99%
“…Consistent with previous research showing that few people seek professional help for gambling problems (see Gainsbury, Hing, & Suhonen, 2013;Suurvali, Cordingley, Hodgins, & Cunningham, 2009), the uptake of self-exclusion is low, with an estimated 9-17% of past-year problem gamblers being enrolled in programs (PC, 2010). The true percentage is likely significantly less, as the estimate does not account for lifetime problem gamblers nor does it account for individuals who enter self-exclusion for other reasons (Griffiths & Auer, 2016;PC, 2010). Studies have identified various xx factors that may prevent problem gamblers from self-excluding.…”
Section: Motivations and Barriers To Self-exclusionmentioning
confidence: 99%